Going to waste – missed opportunities in the battle to improve food security - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2012)
One-third of all food produced for human consumption worldwide is lost or wasted. At a Brussels Development Briefing on ‘Addressing Food Waste in Times of Crisis’, held in June 2012, experts called for greater focus on the issue. This CTA Policy Brief looks at solutions to address food loss in the South, including making affordable post-harvest and processing technologies available to producers and adopting a stronger value chain approach. It also highlights options for tackling the needless squandering of food (mainly a problem in the North), such as legislation, engaging with the private sector (supermarkets) and educating consumers.